Balancing between reality, ideality, and equity: critical reflections from recruiting key informants for qualitative health research - Hanna Luetke Lanfer; Sarah Krawiec; Miriam Schierenbeck; Victoria Touzel; Doreen Reifegerste (BMC Medical Research Methodology)
Abstract Background Key informant interviews (KII) are a widely used method in qualitative health research to gain in-depth insights from individuals with specialized knowledge, experience, or access that is crucial to the research topic. However, there is growing criticism regarding how the selection of key informants is insufficiently described in research. This opacity is problematic as the authority and knowledge of key informants may be given undue weight in research findings, potentially overshadowing other non-expert samples. The resulting imbalance in representation can lead to favoring certain viewpoints while marginalizing others, and thereby reinforcing existing inequities. Methods Using our KII study as an example, we demonstrate how we initially composed an ideal sample based on theoretical considerations and subsequently operationalized it in the field. We employed a selective recruitment strategy informed by intersectional theory, targeting physicians with migration backgrounds from Middle Eastern countries for a study on cancer prevention and screening. Our recruitment process combined direct methods, including database searches and email outreach, with indirect methods like snowball sampling and engagement with multipliers. The recruitment strategy was iterative, allowing for ongoing assessment and adaptation to ensure a diverse and representative sample. Results The KII study successfully recruited 21 physicians with diverse social categories, including different genders, migration backgrounds, language skills, and medical specialties. Direct recruitment was more effective than indirect methods and allowed for greater control in reaching out to specific subsamples. It highlights the importance of flexible and persistent recruitment strategies to achieve the desired sample. Conclusions This KII study underscores the interplay between methodological ideals and the practical realities of recruiting a diverse, carefully composed sample of key informants in health research. Our intersectional approach aimed to ensure equitable representation by considering power dynamics and refining recruitment strategies, while balancing the challenges of real-world fieldwork-such as engaging busy physicians with specific recruitment criteria-with practical adaptability. Our KII study emphasizes the need for ongoing reflexivity to balance ideality and equity with practical feasibility.